2021
DOI: 10.1080/21642850.2021.1951737
|View full text |Cite
|
Sign up to set email alerts
|

Getting back or giving back: understanding caregiver motivations and willingness to provide informal care

Abstract: Background: Informal caregivers are those providing care, which exceeds that which is typically provided, to a relative or friend with care needs. Informal caregiving constitutes the backbone of a society's care supply and with ageing populations the need for informal care is growing. We know little as to why caregivers start caring and continue doing so, yet understanding of motivations and willingness to provide care is important if informal caregivers are to be supported. However, both motivations and willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 150 publications
1
22
0
1
Order By: Relevance
“…Perceived limitations to formal service provision. Perceiving barriers to accessing formal services or considering them as ineffective in addressing caregiver and care recipients' needs Zarzycki & Morrison, 2021) led to a perceived lack of alternative care options and choice for many caregivers. This was key in motivating caregivers to provide care themselves.…”
Section: Theme 2: Societal Norms and Perceived Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived limitations to formal service provision. Perceiving barriers to accessing formal services or considering them as ineffective in addressing caregiver and care recipients' needs Zarzycki & Morrison, 2021) led to a perceived lack of alternative care options and choice for many caregivers. This was key in motivating caregivers to provide care themselves.…”
Section: Theme 2: Societal Norms and Perceived Expectationsmentioning
confidence: 99%
“…Alongside the concept of motivations to provide care, willingness to perform informal care tasks addresses more behavioural aspects of caregiving with current (actual) and future (hypothetical) orientations towards providing support for an individual (Abell, 2001;Zarzycki & Morrison, 2021). Whilst motivations can refer broadly to the reasons and drivers underlying, directing and maintaining caregiving behaviour (Ryan & Deci, 2000;Woolfolk, 2013), willingness to perform care typically addresses certain aspects of caregiver behaviour, for example, willingness to carry out specific emotional and personal care tasks (Abell, 2001;McDonell et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has commonly identified love and affection as the primary motivation for adopting a typically unpaid caregiver role [ 7 , 8 ] along with motives of duty and reciprocity [ 9 ]. However the complexity of dyadic relationships and attachments [ 10 , 11 , 12 , 13 , 14 ], the existence of varying cultural norms, values and obligations [ 15 , 16 ], competing social and economic demands on potential caregivers [ 17 ] and the fact that modern families tend not to be as geographically co-located as in previous generations [ 18 , 19 , 20 , 21 , 22 ] are less typically examined in relation to their influence on caregiver motivations.…”
Section: Introductionmentioning
confidence: 99%
“…Motivations to provide informal care describe the reasons why people engage in caregiving (Zarzycki and Morrison, 2021). Motivations are central to many psychological studies of behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%